Single cell RNA sequencing reveals human tooth type identity and guides in vitro hiPSC derived odontoblast differentiation (iOB) - Hanson-Drury, Sesha; Patni, Anjali P.; Lee, Deborah L.; Alghadeer, Ammar; Zhao, Yan Ting; Ehnes, Devon Duron; Vo, Vivian N.; Kim, Sydney Y.; Jithendra, Druthi; Phal, Ashish; Edman, Natasha I.; Schlichthaerle, Thomas; et al. (Frontiers in Dental Medicine, 2023)
Over 90% of the U.S. adult population suffers from tooth structure loss due to caries. Most of the mineralized tooth structure is composed of dentin, a material produced and mineralized by ectomesenchyme derived cells known as odontoblasts. Clinicians, scientists, and the general public share the desire to regenerate this missing tooth structure. To bioengineer missing dentin, increased understanding of human tooth development is required. Here we interrogate at the single cell level the signaling interactions that guide human odontoblast and ameloblast development and which determine incisor or molar tooth germ type identity. During human odontoblast development, computational analysis predicts that early FGF and BMP activation followed by later HH signaling is crucial. Application of this sci-RNA-seq analysis generates a differentiation protocol to produce mature hiPSC derived odontoblasts in vitro (iOB). Further, we elucidate the critical role of FGF signaling in odontoblast maturation and biomineralization capacity using the de novo designed FGFR1/2c isoform mini binder scaffold C6. Using computational tools, we show on a molecular level how human molar development is delayed compared to incisors. We reveal that enamel knot development is guided by FGF and WNT in incisors and BMP and ROBO in the molars, and that incisor and molar ameloblast development is guided by FGF, EGF and BMP signaling, with tooth type specific intensity of signaling interactions. Dental ectomesenchyme derived cells are the primary source of signaling ligands responsible for both enamel knot and ameloblast development.